Carste em Rochas Não Carbonáticas: contribuição ao estudo geomorfológico em cavernas de arenito da Amazônia Paraense - Freire, Luciana Martins (2017)
The Karst Geomorphology is a branch of geosciences dedicated to investigate nature, genesis and formation processes of natural underground cavities, which include different denominations as caves, shelters, grottos, etc., and understand its related features. The term karst is related to carbonate rocks (limestones, dolomites), but there are also caves developed in siliciclastic rocks (sandstones, conglomerates, shales), metasedimentary (quartzite, iron formation), igneous (granite, basalt), etc. In the Amazon region, which is rich in geomorphological features resulting from systemicinteraction of nature elements stand out caves in sandstones. For example, there is the Speleological Province AltamiraItaituba (Pará state), located in the contact zone of the geological domains of the sedimentary basin of the Amazon and the crystalline basement of the Xingu complex. In this sense, the proposed study, based on the geosystemic analysis of the landscape, presents an amplification of the studies on karst in non-carbonate rocks, contributing to speleological studies in Brazil. The geological structure of the caves of the Province presents notably in friable sandstone of Maecuru Formation belonging to Urupadi Group. Processes involving the formation of the caves are mainly associated with the mechanical action of water (water erosion), although the chemical action of water present in the fundamental role on intergranular dissolution.